2022
DOI: 10.1186/s13063-022-06198-9
|View full text |Cite
|
Sign up to set email alerts
|

Safety, tolerability, and efficacy of monoclonal CD38 antibody felzartamab in late antibody-mediated renal allograft rejection: study protocol for a phase 2 trial

Abstract: Background Antibody-mediated rejection (ABMR) is a cardinal cause of renal allograft loss. This rejection type, which may occur at any time after transplantation, commonly presents as a continuum of microvascular inflammation (MVI) culminating in chronic tissue injury. While the clinical relevance of ABMR is well recognized, its treatment, particularly a long time after transplantation, has remained a big challenge. A promising strategy to counteract ABMR may be the use of CD38-directed treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 50 publications
(78 reference statements)
0
6
0
Order By: Relevance
“…Furthermore, CD38 is an excellent target for the therapy of AL amyloidosis [36]. A team of researchers from the United States and Belgium published a new study on fezatuzumab, demonstrating that it can effectively reduce anti-PLA2R antibody titres in MN patients and that fezatuzumab, as an anti-CD38 monoclonal antibody, has promising therapeutic potential for the treatment of light chain amyloidosis [37]. This could open up new therapy options for people with PMN and AL amyloid nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, CD38 is an excellent target for the therapy of AL amyloidosis [36]. A team of researchers from the United States and Belgium published a new study on fezatuzumab, demonstrating that it can effectively reduce anti-PLA2R antibody titres in MN patients and that fezatuzumab, as an anti-CD38 monoclonal antibody, has promising therapeutic potential for the treatment of light chain amyloidosis [37]. This could open up new therapy options for people with PMN and AL amyloid nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a small phase II prospective randomized trial with an IL-6 inhibitor has shown some promising results in chronic active ABMR (caABMR), and is currently being studied in a large multicenter phase III RCT [ 171 , 172 ]. Additional evidence is emerging on the effectiveness of costimulation blockade, as discussed above, and anti-CD38 therapy in patients with aABMR and caABMR, the latter of which is currently being investigated in a phase II RCT in the form of felzartamab [ 149 , 173 ]. In light of emerging data one may conclude that (early) acute ABMR with dnDSA (but without transplant glomerulopathy) could be more responsive to maintenance treatment optimization as well as PP and IVIG and eventually novel treatment regimens than patients with caABMR or cABMR, albeit all the treatment options have a low amount of supporting evidence.…”
Section: Methodsmentioning
confidence: 99%
“…Felzartamab, a recombinant fully human monoclonal anti-CD38 monoclonal antibody, will be evaluated for safety and tolerability in a multi-center 12-month randomized placebo-controlled parallel-group trial (NCT05021484) ( 146 ). The study hypothesis is that felzartamab will deplete DSA-producing plasma cells thus reducing alloantibody production.…”
Section: Ongoing and Future Clinical Trials To Address Desensitizatio...mentioning
confidence: 99%